Dentists knowledge in oral hygiene instructions to prevent gingivitis in the pregnant women - Garna, Devi Firena; Amaliya, A.; Yubiliana, Gilang (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2011)
The relation between pregnancy and periodontal inflammation has been recognized for many years, therefore, it is important to maintain and promote oral health during pregnancy. The aim of this research is to evaluate dentists knowledge in oral hygiene instructions in preventing gingivitis in the pregnant women. The research has conducted a survey of 40 general dentists in West Bandung District. The survey was done by distributing forms of the questionnaire sent by mail or by telephone interview, and by asking the dentists about their knowledge in oral hygiene instructions regarding the dental care for pregnant women. All of the respondents agreed that oral health during pregnancy was important and therefore it was important to give the Oral Hygiene Instructions (OHI) to the pregnant patients. Two-thirds of dentists (63.8%) agreed that to do scaling was safe, 36.2% of the respondents doubted if Chlorhexidine mouthwash was safe for the use in pregnant women. Almost half of the dentists (57.4%) were doubtful that there was a relationship between periodontitis and preterm birth or low weight birth rate. Dentists as one of the providers of prenatal health care already realized how important it is to keep oral health during pregnancy; however, they doubted if there was a relationship between periodontitis, pre-term birth and low weight birth rate and the safety of using chlorhexidine as an antimicrobial agent during the pregnancy. Providing up to date information and continuing education for dentists knowledge in order to prevent gingivitis during pregnancy.